Plant Diversity in Different Land Use Types at The Peat Hidrological Unit (PHU) of Mendahara – Batanghari River, Jambi Province - Dwisutono, Aji Nuralam; Budi, Sri Wilarso; Istomo, Istomo (Media Konservasi, 2019)
The characteristics of tropical peatlands are still able to form a high diversity of plants. Conversion of tropical peatlands affects the composition of plants. The aim of this study was to find out effect of land use changes to the composition and diversity of plants in the Peat Hydrological Unit (PHU) Mendahara - Batanghari River. The research was conducted in three land use categories, namely secondary forest, coffee plantation, and oil palm plantation (subdivided into oil palm plantation 1 and oil palm plantation 2). In each study location, sample lane 20 m x 200 m were made. Overall, we found 77 species of plants. The results showed   number of plant species decreased due to changes of land use. There are 51 - 53 species of plants in secondary forest areas (out of a total of 58 species) that are not found in oil palm and coffee plantations areas. Differences in composition were also shown in the low value of community similarity (